DESIGNING PUBLIC LIBRARY, IN MEDAN CITY WITH BIOPHILIC ARCHITECTURE - Novrial, Novrial; Munthe, Tegar Erlangga (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
In the context of the Medan City Library, situated in a bustling and densely populated urban area, there is a pressing need for biophilic architectural design to address urban community challenges related to development, building comfort, and the monotony of city life. This approach seeks to respond to the issues posed by biophilic architecture by integrating natural elements into the design to enhance user comfort. Several steps are necessary to finalize the design of a contemporary library using biophilic architecture alongside other structures. These include evaluating the functional roles of additional buildings in architecture, modernizing the approach to library buildings, and applying biophilic principles such as thermal, visual, and natural lighting considerations, natural analogies, and spatial characteristics. The exploration of, digital biophilic architecture has revealed opportunities to adapt biophilic architectural elements into modern forms that align with current advancements, thereby supporting natural elements, natural analogies, and spatial qualities.